Influence of in vitro hemolysis on nucleated red blood cells and reticulocyte counts. Issue 2 (4th October 2012) - Lippi, G.; Pavesi, F.; Cattabiani, C.; Avanzini, P.; Pipitone, S.
Summary Introduction Nucleated red blood cells (NRBCs) and reticulocytes are early and important measures of red blood cells' (RBCs) turnover, but little is known on how spurious hemolysis may affect the reliability of these parameters. Materials and Methods Ten EDTA‐anticoagulated samples were divided into three aliquots. The first was immediately tested, where;?>as the others (defined A and B) were mechanically hemolyzed by aspiration 5 and 10 times through a small‐gauge needle. RBC, NRBC, and reticulocyte counts were performed on Sysmex XE‐2100. Results An increasing amount of hemolysis was produced in hemolyzed aliquots A and B. The RBC and reticulocyte counts progressively decreased from the nonhemolyzed sample to hemolyzed aliquots 'A' and 'B'. The NRBC count increased in 3 of the 10 samples and decreased in the remaining seven. Conclusions Hemolysis of venous blood samples may seriously jeopardize NRBC and reticulocyte counts.